Salmonella muenchen osteomyelitis in a white boy with sickle cell disease - Aksoycan, Namık; Özsoylu, Şinasi; Gülmezoğlu, Ekrem (The Turkish Journal of Pediatrics, 1958)
We have described a patient who presented the now well known combination of sickle cell disease complicated by Salmonella osteomyelitis. He was of interest, we felt, because we have found no previous report of this combination occurring in a white individual. In addition, the particular microorganism, Salmonella muenchen, has not previously been isolated under such circumstances. Finally, this child presented another interesting complication of sickle cell disease in that there had apparently been aseptic necrosis of the os capitatum with complete resorption.